SUPPLEMENTARY DATA FOR: SLC38A10 Regulate Glutamate Homeostasis and modulate the AKT/TSC2/mTOR Pathway in mouse cortex cells - Tripathi, Rekha (Uppsala University, 2021)
SUPPLEMENTARY DATA -PAPER IV

SLC38A10 Regulate Glutamate Homeostasis and modulate the AKT/TSC2/mTOR Pathway in mouse cortex cells.

PDF and Excel files.

The dataset was originally published in DiVA and moved to SND in 2024.

SUPPLEMENTARY DATA -PAPER IV

SLC38A10 Regulate Glutamate Homeostasis and modulate the AKT/TSC2/mTOR Pathway in mouse cortex cells.

PDF and Excel files.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
SUPPLEMENTARY DATA FOR: SLC38A10 Regulate Glutamate Homeostasis and modulate the AKT/TSC2/mTOR Pathway in mouse cortex cells
Keywords: Biology with specialization in Molecular Biology; Biologi med inriktning mot molekylärbiologi; Biological Sciences; Biologi